Letter : Spanish seamen - Reed, George
025a-0090-001 Telegraphic Address: "searoving, lamb, london" Telephone No: WATerloo 5906. (Five Lines) National Union of Seamen REGISTERED TRADE UNION NO 1493 APPROVED SOCIETY CERTIFICATE NO 128 Affiliated to the Labour Party, International Transportworkers Federation, Trades Union Congress National Maritime Board. (Sailors, Firemen and Catering Panels) Executive Officers: General Secretary W.R.SPENCE C.B.E. Asst. General Secretary: G. REED General Treasurer: J B WILSON Registered Offices: ST GEORGES HALL, WESTMINSTER BRIDGE ROAD. LONDON S.E.1. Please Quote in Reply Your Ref HVT/AC/198 Our Ref GR/MLA. ALL COMMUNICATIONS MUST BE ADDRESSED TO THE GENERAL SECRETARY Mr.H.V.Tewson, May 26th 1939 Trades Union Congress, Transport House, Smith Square, LONDON, S.W.1. Dear Mr. Tewson, SPANISH SEAMEN. I beg to acknowledge receipt of your letter of the 23rd instant with cheque enclosed for £390. in settlement of the accounts in respect of the payments to Spanish Seamen for the period closing May 13th 1939. I appreciate very much the sentiments expressed in your letter to the officers of the Union for making arrangements in respect of these payments, and I think you will appreciate we did our best under very difficult circumstances. I am sure I do not envy you dealing with these matters, and I hope that the Trades Union Congress will succeed in getting these Spanish refugee seamen repatriated to some approved domicile outside the United Kingdom. Yours faithfully, George Reed Assisted General Secretary 292/946/25a/90